Capitalizing IP– Security Interest and Securitization of Trademarks - Shaaban, Eslam (Université d'Ottawa / University of Ottawa, 2020)
One of the main barriers for any innovator or entrepreneur is a lack of funding for their projects. In many cases innovators and entrepreneurs do not have valuable assets that could be presented as collateral to lenders. As well, in many cases innovators and entrepreneurs are not aware of the value of their IP portfolios and how these properties could be developed and economically utilized. Canada is a country with ambitious plans to encourage innovation and enhance economic growth. It is important that Canada develop comprehensive legal and policy frame-works that help innovators and IP creators not only to protect their assets but to use them to raise capital. In fact, the Government of Canada, as investigated in this dissertation, is making significant efforts to develop its intellectual property and innovations paradigms. How-ever, there are barriers and pitfalls in the legal and policy frameworks governing security interests in IP assets in Canada. While there are some minor differences, these problems are shared by most IP assets. In this dissertation, I analyze the pitfalls and barriers in using trademarks, one of the most popular IP assets, as security interests, and do so not only from a theoretical point of view but also from a practical one. In the theoretical analysis I examine the Canadian legal frameworks governing security interests in trademarks as well as those in the United States. I conducted empirical research with all concerned parties having an interest in security interests in trademarks: Canadian lawyers, bankers, government officials and other professionals. This helped me to highlight the gaps and pitfalls in Canadian regulatory and policy frame-works governing security interests in trademarks. The interviews I conducted with these stakeholders also helped me to better shape recommendations to develop and reform the cur-rent frameworks. This dissertation paves the way for future research related to other IP assets such as patents, copyrights and domain names. It also highlights other key points that could help develop and reform current Canadian IP policies and regulations.
Keywords: Trademarks; Security interests in IP in Canada and the U.S.; Security interests in trademarksin Canada and the U.S.; Capitalizing trademarks; Capitalizing IP; Blockchain; financing of innovations; Securitization of IP